Influence of product quality, price, and quality of service to customer satisfaction (study on Resto Solaria Mall Lippo Cikarang) - Erdi Erdi; Dadang Heri Kusumah; Sumardjono Sumardjono; Dimas Ari Darmantyo (STIE Binaniaga, 2021)
This study aims to partially examine the effect of product quality on consumer satisfaction, partially examine the effect of price on consumer satisfaction, and partially examine the effect of service quality on customer satisfaction, at the same time conducted at SOLARIA Resto Mall Lippo Cikarang. The sampling method used is non-probability sampling, namely quota sampling. The sample of this study was 100 respondents who had visited the SOLARIA Mall Lippo Cikarang restaurant, and these respondents distributed online questionnaires via google form. This research is based on multiple linear regression analysis, with the help of SPSS statistical procedures, to test the validity and reliability of research tools in the form of partial test (t test) and simultaneous test (F test), classical assumption test and hypothesis test. hypothesis test (F test), the results obtained are product quality has a positive and significant effect on consumer satisfaction. There is a positive and significant effect of price on consumer satisfaction. There is a positive and significant effect of service quality on customer satisfaction. There is a simultaneous influence of product quality, price, and service quality on consumer satisfaction at Resto SOLARIA Mall Lippo Cikarang. This shows that all hypotheses in this study are accepted.